EXPERIENCES OF SOCIAL ISOLATION AMONG ELDERLY WITH DISABILITIES IN CHINA: A QUALITATIVE STUDY - Zhang, Yanxiao (LIFE: International Journal of Health and Life-Sciences, 2024)
Social isolation is considered to be an important indicator of public health, which is closely related to health outcomes such as readmission rate, co-morbidity, mortality, depression, cognitive decline and quality of life of disabled elderly people. However, not enough is known about the experiences of social isolation in older persons with disabilities.This qualitative study aimed to explore the experiences of social isolation in disabled older adults. Disabled people over 60 years old were purposively sampled to participate in a semi-structured interview steered by a topic guide to collect data. Interviews were audio recorded, and analysed using Colaizzi's seven-step analysis. Demographic and clinical data of the subjects were investigated by questionnaire before the semi- structured interview. Disabled elderly were recruited in Shamen Community Health Service Centre, Henan Province, China. One-on-one face-to-face interviews were conducted with participants in the central office. 12 disabled seniors participated in semi- structured interviews. Six themes were extracted from data. These themes were as follows: (1) Self-factors that produce social isolation;(2)Family factors that produce social isolation;(3)Environmental factors that produce social isolation;(4)The inner experience of social isolation;(5)Social support strategies to prevent social isolation;(6)Positive psychological adjustment to disability. The experiences of social isolation of disabled elderly people are influenced by many factors. Improving this situation requires helping them to understand the dangers of social isolation, improve self-efficacy, develop new attitudes of social connection, and build strong, supportive and sustainable social connections with other older adults.